Integration of Islamic Education Values and Fiqh al-Bi’ah in Cultivating Environmentally Responsible Character - Muzakki, Hawwin; Moh. Arif; Mamah, Manavavee (IAIN Ponorogo, 2025)
This study highlights the critical role of Islamic education in shaping students’ environmentally responsible character – an urgent imperative in light of escalating environmental degradation. This study aims to examine the integration of Islamic educational values and fiqh al-bi’ah into the curriculum, analyze the implementation of character-building programs that promote environmental awareness, and explore the implications of this integration for developing students’ environmentally caring character. Using a qualitative multisite approach, data were gathered through interviews, observations, and documentation involving teachers, students, and school officials at MTsN 8 Blitar and MTsN 2 Kediri. Thematic analysis revealed that integrating Islamic educational values and fiqh al-bi’ah significantly improved students’ ecological responsibility. Activities such as tree planting, composting, and school-wide waste management fostered consistent pro-environmental behavior grounded in religious teachings. The research concludes that this integration encourages active student participation and awareness by embedding Islamic environmental ethics into both curricular and extracurricular activities in a systematic, multidisciplinary, and collaborative manner. This approach builds environmentally conscious character and aligns with broader goals such as sustainable development. The study recommends replicating this model in other Islamic educational institutions to promote ecological awareness and responsibility among future generations.